La dictadura franquista (1936-1975) : textos y documentos / José Manuel Sabín Rodríguez ; revisión científica, Elena Hernández Sandoica - Hernández Sandoica, Elena; Sabín Rodríguez, José Manuel (España sin espejo ; 10)
Cronología: p. 401-442Bibliografía en cada capítulo